Criminal Procedure Law Reform in Indonesia as a Step Towards a Fairer and More Effective Justice System - Kimico Margaretha Tjhia; Azis Budianto (Riviera Publishing, 2025)
The implementation of the Criminal Procedure Law in Indonesia is a critical part of recognizing a fair criminal justice system under human rights principles. An ideal legal system should provide legal protection for every individual involved in the criminal process, whether suspect, defendant, or victim. However, in practice, there are still various challenges that hinder the implementation of Criminal Procedure Law effectively and fairly. Various problems such as inconsistent law enforcement, violations of the principle of fair trial, and limited access to justice are issues that must be addressed. This study aims to analyze the implementation of Criminal Procedure Law in Indonesia and identify the main challenges faced in realizing a fair legal system. The approach used in this study is the normative legal method with a focus on the analysis of laws and regulations and literature studies related to Criminal Procedure Law. The data used in this study consists of primary data in statutes and regulations, such as the Criminal Procedure Code (KUHAP), as well as secondary data from law journals, academic literature, and previous research results. Data collection techniques are carried out through literature studies by analyzing various relevant legal documents and academic literature. This approach aims to provide a comprehensive picture of the applicable regulations and the challenges that arise in their implementation. Through this analysis, the research is expected to contribute to the development of a fairer and more effective criminal law system in Indonesia, as well as offer concrete recommendations for relevant stakeholders.